Radical resection and outcome for malignant tumors of the pancreatic body and tail - Han, Shao-Liang (The WJG Press and Baishideng, 2009)
AIM: To analyze the factors influencing radical (R0) resection rate and surgical outcome for malignant tumor of the pancreatic body and tail. METHODS: The clinical and operative data and follow-up results of 214 pancreatic body and tail cancer patients were analyzed retrospectively. RESULTS: One hundred and twenty/214 pancreatic body and tail cancer patients underwent surgical treatment; the overall resection rate was 59.2% (71/120), and the R0 resection rate was 40.8% (49/120). Compared with non-R0 treatment, the patients receiving an R0 resection had smaller size tumor (P < 0.01), cystadenocarcinoma (P < 0.01), less lymph node metastasis (P < 0.01), less peri-pancreatic organ involvement (P < 0.01) and earlier stage disease (P < 0.01). The overall 1-, 3- and 5-year survival rates for pancreatic body and tail cancer patients were 12.7% (25/197), 7.6% (15/197) and 2.5% (5/197), respectively, and ductal adenocarcinoma patients had worse survival rates [15.0% (9/60), 6.7% (4/60) and 1.7% (1/60), respectively] than cystadenocarcinoma patients [53.8% (21/39), 28.2% (11/39) and 10.3% (4/39)] (P < 0.01). Moreover, the 1-, 3- and 5-year overall survival rates in patients with R0 resection were 55.3% (26/47), 31.9% (15/47) and 10.6% (5/47), respectively, significantly better than those in patients with palliative resection [9.5% (2/21), 0 and 0] and in patients with bypass or laparotomy [1.2% (1/81), 0 and 0] (P < 0.01). CONCLUSION: Early diagnosis is crucial for increasing the radical resection rate, and radical resection plays an important role in improving survival for pancreatic body and tail cancer patients.